Comparison of various cooling systems for a tractor cab in tropical climate - Panigrahi, Suranjan; Gupta, Chandra P.; Gee-Clough, D.; Singh, Gajendra; Royal Norwegian Government (Bangkok : Asian Institute of Technology, 1986)
As the Asian farmers can not afford to pay for the costly air conditioned cab on the tractor, it was thought worth while to investigate the technical feasibility of providing thermal comfort to the operator , by low-cost methods other than air-conditioning. With this view in mind , an experimental low cost tractor cab was constructed and eight sensible and two evaporative cooling systems were studied for their technical feasibility in providing thermal comfort inside a tractor cab during the summer of1986 in the experimental farm of Asian Institute of Technology, Bangkok. It was concluded that the system (cab with four side open , all the sides with external shade and with fan cooling having air movement from inside to outside ) was found to be t he most effective sensible cooling system The cab with shade and evaporative cooling was found to be the best of all ~he systems. The later could achieve an average inside temperature of 29-30 degree C with inside heat stress index value below 30 in a summer environment which has outside dry bulb temperature of 39 - 40 degree C and outside heat stress index of 140 Therefore it is recommended to adopt the evaporative cooling system with shade both for economy and comfort of the operator in tropical climate.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Tractors